Altered Lipid Profiles and Vaccine Induced-Humoral Responses in Children Living With HIV on Antiretroviral Therapy in Tanzania - Mbuya, Wilbert; Mwakyula, Issakwisa; Olomi, Willyelimina; Agrea, Peter; Nicoli, Francesco; Ngatunga, Cecilia; Mujwahuzi, Leodegard; Mwanyika, Paul; Chachage, Mkunde (Frontiers in Cellular and Infection Microbiology, 2021)
People living with HIV, even under therapy, have a high burden of age-related co-morbidities including an increased risk of dyslipidemia (which often predisposes to cardiovascular diseases) and immune-aging. In this study, lipid profiles and antibody responses to measles and pertussis toxin vaccines were compared between ART experienced HIV+ children (n=64) aged 5-10 years, and their age- and sex-matched HIV- controls (n=47). Prevalence of high-density lipoprotein cholesterol (HDL-c) and triglyceride-driven dyslipidemia was higher among treated HIV+ children than in controls (51.6% vs 27.7% respectively, p < 0.019). In a multivariate Poisson regression model adjusted for age, sex and BMI, the association between low HDL-c, hypertriglyceridemia and HIV remained significantly high (for HDL-c: ARR: 0.89, 95% CI: 0.82 – 0.96, p = 0.003; for triglycerides: ARR: 1.54, 95% CI: 1.31 – 1.81, p < 0.001). Among HIV+ children, the use of lopinavir/ritonavir, a protease-based antiretroviral therapy was also associated elevation of triglyceride levels (p = 0.032). Also, HIV+ children had a 2.8-fold reduction of anti-measles IgG titers and 17.1-fold reduction of anti-pertussis toxin IgG levels when compared to HIV- children. Our findings suggest that dyslipidemia and inadequate vaccine-induced antibody responses observed in this population of young African HIV+ children might increase their risk for premature onset of cardiovascular illnesses and acquisition of preventable diseases.